Cattle and prairie dog on prairie dog town - Gunther, Deb, photographer (Colorado State University. Libraries, 2001)
Two cows grazing on a prairie dog town, with a visible prairie dog.
Keywords: prairie dog; SGS; cattle; animals; prairie dog town; grazing